PENGARUH PENGGUAAN MEDIA TALI DALAM LATIHAN TERHADAP TEKNIK DASAR TENDANGAN T PENCAK SILAT - Pikjen Paulus Simbolon; Edi Purnomo; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem in this research is that the dilator behind the practice is still making a lot of T kick mistakes, the stance of the horses is not strong enough, there is no stomping of the instep, the body is unbalanced and the legs when doing a T kick is not straight. The research aims to study whether there is reinforcement of the use of rope media in training the basic technique of kicking deer athletes This research was carried out in all colleges with a chain of branches at the Jalan Komyos Sudarso, Gg cantur citizen. The research method used was research with the design of One Group Pretest and Posttst. Sampling of all deer chain deer athletes collected 24 people. Analysis of the data used in this study t-test The results of this study are the influence of media related to the basic technique of T in the chain deer college based on the assessment of tcount> ttabe which is equal to 7.53> 1.713. With an average value at pretest of 69 and an average value at posttst of 77 thus the results of this study can be summarized from Ha = accepted and Ho = rejected. Means there is the influence of the media rope on the kick technique T.Keywords: Rope media, T kick.